Research on Water Pollution Prevention and Control and Countermeasures for Rural and Urban Rivers - Li, Qiuyan (International Journal of Natural Resources and Environmental Studies, 2026)
Water pollution is one of the major environmental problems facing the world, posing a serious threat to human health and the ecosystem. The sources of water pollution mainly include industrial emissions, agricultural activities, and urban domestic sewage, and its impacts involve drinking water safety and ecosystem destruction. Rural areas are the foundation for building a "Beautiful China" and play an important role in ecological civilization construction; urban rivers are a key link in building urban ecological environments and an important part of urban ecosystems. Therefore, sufficient attention should be given to water pollution problems in rural and urban areas, and effective measures should be taken to continuously optimize the ecological environment. Based on the analysis of the existing problems and causes of water pollution in rural and urban rivers, this article explores the path of water pollution prevention and control from the perspective of sustainable development and summarizes the corresponding prevention and control measures.